INTERDEPENDENCE ARMY, WAR AND THE ECONOMY AS THE BASIS OF PREPARATION OF DEFENSE TO COUNTRY - Semenov, S. S.; Gegechkori, О. V.; Ryutin, V. V. (Honor and Law, 2019)
The issue of interdependence of concepts "army", "war", "economy" is analyzed. The system deals with special characteristics such as the institute states army. The peculiarities of the relationship of the army and the economy in peacetime and wartime.